The oral Ca/calmodulin‐dependent kinase II inhibitor RA608 improves contractile function and prevents arrhythmias in heart failure. (20th July 2020) - Mustroph, Julian; Drzymalski, Marzena; Baier, Maria; Pabel, Steffen; Biedermann, Alexander; Memmel, Bernadette; Durczok, Melanie; Neef, Stefan; Sag, Can Martin; Floerchinger, Bernhard; Rupprecht, Leopold; Schmid, Christof; et al.
Abstract: Aims: Excessive activation of Ca/calmodulin‐dependent kinase II (CaMKII) is of critical importance in heart failure (HF) and atrial fibrillation. Unfortunately, lack of selectivity, specificity, and bioavailability have slowed down development of inhibitors for clinical use. We investigated a novel CaMKIIδ/CaMKIIɣ‐selective, ATP‐competitive, orally available CaMKII inhibitor (RA608) on right atrial biopsies of 119 patients undergoing heart surgery. Furthermore, we evaluated its oral efficacy to prevent deterioration of HF in mice after transverse aortic constriction (TAC). Methods and results: In human atrial cardiomyocytes and trabeculae, respectively, RA608 significantly reduced sarcoplasmic reticulum Ca leak, reduced diastolic tension, and increased sarcoplasmic reticulum Ca content. Patch‐clamp recordings confirmed the safety of RA608 in human cardiomyocytes. C57BL6/J mice were subjected to TAC, and left ventricular function was monitored by echocardiography. Two weeks after TAC, RA608 was administered by oral gavage for 7 days. Oral RA608 treatment prevented deterioration of ejection fraction. At 3 weeks after TAC, ejection fraction was 46.1 ± 3.7% (RA608) vs. 34.9 ± 2.6% (vehicle), n = 9 vs. n = 12, P < 0.05, ANOVA, which correlated with significantly less CaMKII autophosphorylation at threonine 287. Moreover, a single oral dose significantly reduced inducibility of atrial and ventricular arrhythmias in CaMKIIδ transgenic mice 4 h after administration. Atrial fibrillation was induced in 6/6 mice for vehicle vs. 1/7 for RA608, P < 0.05, ' n − 1' χ 2 test. Ventricular tachycardia was induced in 6/7 for vehicle vs. 2/7 for RA608, P < 0.05, ' n − 1' χ 2 test. Conclusions: RA608 is the first orally administrable CaMKII inhibitor with potent efficacy in human myocytes. Moreover, oral administration potently inhibits arrhythmogenesis and attenuates HF development in mice in vivo .